Simple Incinerator Model with Wet Coconut Filters for Mask Waste Treatment in Banjarbaru, South Kalimantan - Sumi Kartika; Husaini; Eko Suhartono; Meitria Syahadatina Noor; Nelly Al Audhah (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: Based on data from the 2019 Population Census, the population of Banjarbaru City is 262,719 people; if as many as 50% of the people of Banjarbaru City use masks, approximately 135,200 masks are generated per day, or 4,056,000 masks waste per month. To analyze the effect of the incinerator on CO, CO2 and NO2 exhaust gases of mask waste before using wet coconut fiber and after using wet coconut fiber. Methodology: This research method uses the experimental method. The experimental design in this study is a pre-experimental design by providing treatment and measuring the results of the treatment carried out pretest and post-test. The research was conducted at the Mustika Graha Asri Housing Complex RT 11 RW 01 Loktabat Utara Banjarbaru, South Kalimantan, in April 2022. Findings: From the results of statistical data processing using the paired t-test method, CO exhaust gas was obtained with a significance value of 0.853 (p> 0.05), CO2 with a significance value of 0.002 (p< 0.05) and NO2 with a significance value of 0.801 (p> 0.05). The exhaust gas that has a significant difference before and after using the wet coconut fiber filter is CO2 exhaust gas, while there is no significant difference between CO gas and NO2 exhaust gas. Many shortcomings still need to be addressed so that the combustion process in this simple incinerator is more optimal. Implications/Novel Contribution: The present study advances knowledge by comprehensively summarizing mask waste treatment using wet coconut filters. Additionally, this research offers useful information on the entire installation procedure and necessary tools.